President’s Message: Journeys and the Joy of Circles - Stephens, Gloria (Operating Room Nurses Association of Canada Journal, 1992)
When one sets out on a journey, one usually checks to see that they have all the ingredients to make a successful trip - maps, tickets, reservations, a plan. Some may think of every detail, others need guidance and assurance to set them on the right course.